Building a CTU Orientation Handbook iPad® application for first-year residents - Chan, James; Desjardins, Isabelle; Rashidi, Babak; Jiang, Di Maria; Yang, Fan (Canadian Medical Education Journal, 2019)
Background: The General Internal Medicine Clinical Teaching Unit (CTU) is a challenging rotation for new residents and the optimal format of orientation has not been determined. We hypothesized that an iPad®application (app) would be a useful reference tool after residents completed their traditional large group orientation. Methods: Postgraduate year 1 (PGY1) residents were sent a link to download the free app one week before the start of their rotation. A pre-usage survey at initial login collected basic demographics. Usage data was collected to determine the sections, duration, and the timeframe from which the app was utilized. Results: Pre-usage survey data revealed that 63% of participants were female, 69% felt the app would improve orientation, and 94% were comfortable using mobile technology for medical education. Usage data showed “Teaching Sessions and Schedules,” “The Consult Note,” and “Admission Orders” were the three sections most commonly used. The most usage was during the evening call shift (10pm to 6am), followed by the morning shift (6am to 5pm). Conclusion: The CTU Orientation App was a useful supplement to the traditional orientation. Researchers may not be able to predict what content would be most valuable in an iPad® app, thus pre-development needs-assessments and usage feedback are crucial.